Akt Is S-Palmitoylated: A New Layer of Regulation for Akt - Blaustein, Matías; Piegari, Estefanía; Martínez Calejman, Camila; Vila, Antonella; Amante, Analía; Manese, María Victoria; Zeida, Ari; Abrami, Laurence; Veggetti, Mariela; Guertin, David A.; van der Goot, F. Gisou; Corvi, María Martha; et al. (Frontiers in Cell and Developmental Biology, 2021)
The protein kinase Akt/PKB participates in a great variety of processes, including translation, cell proliferation and survival as well as malignant transformation and viral infection. In the last few years, novel Akt posttranslational modifications have been found. However, how these modification patterns affect Akt subcellular localization, target specificity and function is not thoroughly understood. Here, we postulate and experimentally demonstrate by acyl-biotin exchange (ABE) assay and 3H-palmitate labeling that Akt is S-palmitoylated, a modification related to protein sorting throughout subcellular membranes. Mutating cysteine 344 into serine blocked Akt S-palmitoylation and diminished its phosphorylation at two key sites, T308 and T450. Particularly, we show that palmitoylation-deficient Akt increases its recruitment to cytoplasmic structures that colocalize with lysosomes, a process stimulated during autophagy. Finally, we found that Akt1 cysteine 344 is important for proper Akt function, since Akt1-C344S was unable to support adipocyte cell differentiation in vitro. These results add an unexpected new layer to the already complex Akt molecular code, improving our understanding of cell decision-making mechanisms such as cell survival, differentiation and death.